A Strengthening Strengthening Microalgae Biodiesel Production Capacity Based on Strain Selection for Chaetoceros amini, Nannochloropsis oculata and Nitzschia spp. - Suripto Suripto; Lalu Japa (Jurnal Penelitian Pendidikan IPA, 2024)
Increasing microalgae biodiesel production through improvement of biomass production is reversible and is often considered economically unprofitable. This research aims to determine the effect of various levels of media salinity stress in producing microalgae strains that have higher oil content than the original population. Three species of microalgae are known to be capable of producing biodiesel, namely Chaeticheros amini, Nannochloropsis oculata and Nitzschia spp. isolated from Sekotong coastal waters, West Lombok, then cultivated in bioreactor systems for seven days with salinity stress treatment to produce strains. The resulting strains were cultivated again, but without salinity stress. Microalgae cell density was observed every day and harvested on the seventh day. The resulting microalgae biomass was extracted in stages to produce biodiesel oil. The results showed that after cultivation under salinity stress, S20, S25, S30, and S35 strains were produced from each of these species. Under salinity stress, all strains except S25 of Nitzschia spp. showed a higher maximum cell density compared to the original population and were reversible respectively. Each of the S25 strains of C. amini and N. oculata, S20 and S25 strains of Nitzschia spp., had a higher oil content than the original population, each of which was permanent